2022
DOI: 10.1186/s13045-022-01245-z
|View full text |Cite
|
Sign up to set email alerts
|

Reductive TCA cycle catalyzed by wild-type IDH2 promotes acute myeloid leukemia and is a metabolic vulnerability for potential targeted therapy

Abstract: Background Isocitrate dehydrogenase-2 (IDH2) is a mitochondrial enzyme that catalyzes the metabolic conversion between isocitrate and alpha-ketoglutarate (α-KG) in the TCA cycle. IDH2 mutation is an oncogenic event in acute myeloid leukemia (AML) due to the generation of 2-hydroxyglutarate. However, the role of wild-type IDH2 in AML remains unknown, despite patients with it suffer worse clinical outcome than those harboring mutant type. Methods ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Forward TCA is a catabolic pathway, while IDH1- and IDH2-mediated reverse TCA is the anabolic process of adding H and C. This process, known as reductive carboxylation, involves adding C of CO 2 directly to α-KG to form 6-C isocitrate, which isomerizes to form citrate. Studies have confirmed that the active IDH2-mediated reductive TCA cycle in acute myeloid leukemia (AML) cells promotes the conversion of α-KG to isocitrate/citrate, thereby facilitating the synthesis of lipids from glutamine [ 13 ].…”
Section: The Role Of Wild-type Idh1 and Idh2 In Cellular Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Forward TCA is a catabolic pathway, while IDH1- and IDH2-mediated reverse TCA is the anabolic process of adding H and C. This process, known as reductive carboxylation, involves adding C of CO 2 directly to α-KG to form 6-C isocitrate, which isomerizes to form citrate. Studies have confirmed that the active IDH2-mediated reductive TCA cycle in acute myeloid leukemia (AML) cells promotes the conversion of α-KG to isocitrate/citrate, thereby facilitating the synthesis of lipids from glutamine [ 13 ].…”
Section: The Role Of Wild-type Idh1 and Idh2 In Cellular Metabolismmentioning
confidence: 99%
“…Inhibition of IDH2 with AGI-6780 in mice carrying AML xenografts demonstrated significant therapeutic effects and potential clinical applications. The study also suggested that IDH2 inhibition could transform cancer treatment from cytotoxic to precision therapy and fundamentally change the cancer treatment landscape [ 13 ]. Recent research has found that shRNA inhibition of wild-type IDH2 increased α-KG, decreased c-Myc (an important oncogene), and suppressed AML viability and proliferation [ 13 ].…”
Section: Research Progress Of Wild-type Idh2 In Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…The observations that tumorigenesis often requires multiple hits suggest that K‐ras mutation likely needs the coordination of other molecular events that enable adaptive cellular metabolism for a full malignant transformation. Based on our previous study on the impact of K‐ras on mitochondrial metabolism [ 1 , 5 ] and our recent findings that mitochondrial isocitrate dehydrogenase 2 (IDH2) could promote the “reverse” flow of the tricarboxylic acid (TCA) cycle from α‐KG to isocitrate and enhance the survival and proliferation of acute myeloid leukemia cells [ 6 ], we investigated the potential role of IDH2 in metabolic adaptation during K‐ras‐driven tumorigenesis.…”
mentioning
confidence: 99%